Analysis of Operational Performance and Service of the Jenggala Commuter Train (Route Surabaya Kota – Mojokerto) - Zainuddin, Hafid; Judiono, Judiono; Xu, Shanshan (Journal of Moeslim Research Technik, 2024)
This research aims to analyze the operational performance and facilities availability at the stations for the Jenggala Commuter Train connecting Surabaya Kota with Mojokerto. Through data collection and analysis, this study will evaluate issues frequently experienced by passengers such as improper departure times, delays, overcrowding, and ticket availability. Additionally, it will assess the service provided by the operators regarding passenger satisfaction with the Jenggala commuter service. The next step involves comparing the analysis results with applicable standards to identify appropriate solutions and recommendations to enhance the efficiency and quality of mass transportation services in urban areas of Indonesia, particularly in East Java. It is hoped that the findings of this research will significantly contribute to improving sustainability and the quality of life for communities through the enhancement of existing transportation systems. The operational performance has been assessed through several parameters. It was found that the load factor and punctuality of journeys have met the established standards. However, travel speed has not yet reached the desired standard. Through the Importance Performance Analysis (IPA) method, an evaluation of the Jenggala commuter train service was conducted by considering both low and high priority service attributes. This aims to ensure that the service performance meets the needs of passengers. The results of the passenger satisfaction level analysis using the Customer Satisfaction Index (CSI) method indicate that the overall satisfaction rating for the Jenggala commuter train service falls within the "satisfied" category. Thus, these findings provide insights into areas where operational performance can be improved and offer an understanding of passenger needs and expectations that can serve as a focus for improvement in the future.